Begging Phenomenon Between the Destitution Plight and the Material Greedy - A Field Study in the City of Baghdad (Journal of the College of Education for Women, 2019)
Begging is an ancient social phenomenon since the Man's creation. It was simple at its beginning to get a living and the family needed, but presently, this simple social phenomenon converted to a big phenomenon which controlled by competent groups away from the values and principles. Their doings are far from humanity representing by the cutting of a hand or a foot and facial distortion or removed eye as a way of attracting people's emotions to get material and incorporeal helps; these doings became a trade which is exchanged by slave traders. Furthermore, different illegal and greedy methods were followed as a way of blackmailing others; contrariwise other cases of begging are doing by a people who real poor and needy. In this case, there will be a chaos and we can't distinguish them; it means that there has been a mix-up between the begging for the need and the begging because of greedy, subsequently, this will lead to prevent charity.The field research concerning this subject showed that some people particularly the elderly ones were beggars since their childhood. Additionally, the economic reasons play a great role in practicing the profession of begging; as well as the psychological status and the family circumstances create weak and greedy people, whereas with some other people, their faces clarify their misery status because of their poverty.